Cost-effectiveness of ceritinib in patients previously treated with crizotinib in anaplastic lymphoma kinase positive (ALK+) non-small cell lung cancer in Canada. (2nd October 2016) - Hurry, Manjusha; Zhou, Zheng-Yi; Zhang, Jie; Zhang, Chenxue; Fan, Liangyi; Rebeira, Mayvis; Xie, Jipan
Abstract: Background: To assess the cost-effectiveness of ceritinib vs alternatives in patients who discontinue treatment with crizotinib in anaplastic lymphoma kinase-positive (ALK+) non-small cell lung cancer (NSCLC) from a Canadian public healthcare perspective. Methods: A partitioned survival model with three health states (stable, progressive, and death) was developed. Comparators were chosen based on reported utilization from a retrospective Canadian chart study; comparators were pemetrexed, best supportive care (BSC), and historical control (HC). HC comprised of all treatment alternatives reported. Progression-free survival and overall survival for ceritinib were estimated using data reported from single-arm clinical trials (ASCEND-1 [NCT01283516] and ASCEND-2 [NCT01685060]). Survival data for comparators were obtained from published clinical trials in a NSCLC population and from a Canadian retrospective chart study. Parametric models were used to extrapolate outcomes beyond the trial period. Drug acquisition, administration, resource use, and adverse event (AE) costs were obtained from databases. Utilities for health states and disutilities for AEs based on EQ-5D were derived from literature. Incremental costs per quality-adjusted life year (QALY) gained were estimated. Univariate and probabilistic sensitivity analyses were performed. Results: Over 4 years, ceritinib was associated with 0.86 QALYs and total direct costs of 89, 740 for the post-ALK population. The incremental cost-effectiveness ratio (ICER) was 149, 117 comparing ceritinib vs BSC, 80, 100 vs pemetrexed, and 104, 436 vs HC. Additional scenarios included comparison to docetaxel with an ICER of 149, 780 and using utility scores reported from PROFILE 1007, with a reported ICER ranging from 67, 311 vs pemetrexed to 119, 926 vs BSC. Due to limitations in clinical efficacy input, extensive sensitivity analyses were carried out whereby results remained consistent with the base-case findings. Conclusion: Based on the willingness-to-pay threshold for end-of-life cancer drugs, ceritinib may be considered as a cost-effective option compared with other alternatives in patients who have progressed or are intolerant to crizotinib in Canada.